Ribonucleoprotein complexes of hepatitis delta virus. - Ryu, W S (1993)
Human hepatitis delta virus (HDV) is a subviral satellite agent of hepatitis B virus (HBV). The envelope proteins of HDV are provided by the helper virus, HBV, but very little is known about the internal structure of HDV. The particles contain multiple copies of the delta antigen and an unusual RNA genome that is small, about 1,700 nucleotides in length, single stranded, and circular. By using UV cross-linking, equilibrium density centrifugation, and immunoprecipitation, we obtained evidence consistent with the interpretation that delta antigen and genomic RNA form a stable ribonucleoprotein (RNP) complex within the virion. Furthermore, electron-microscopic examination of the purified viral RNP revealed a roughly spherical core-like structure with a diameter of 18.7 +/- 2.5 nm. We also isolated HDV-specific RNP structures from the nuclei of cells undergoing HDV genome replication; both the genome and antigenome (a complement of the genome) of HDV were found to be in such complexes. From the equilibrium density analyses of the viral and nuclear RNPs, we were able to deduce the number of molecules of delta antigen per molecule of HDV RNA. For virions, this number was predominantly ca. 70, which was larger than for the nuclear RNPs, which were more heterogeneous, with an average value of ca. 30.